Relationship between Self-efficacy and Learning Motivation with Student Learning Outcomes on Endocrine System Material at La Tansa High School - Miharja, Jajang; Fadila, Naritsa; Survani, Rifki (Bioedunis Journal, 2024)
This research aims to determine the relationship between self-efficacy, learning motivation, and student learning outcomes in the endocrine system material at La Tansa High School. This study uses a quantitative approach. The instruments used in data collection were questionnaires and test questions. This research was conducted from 17 to 25 June 2023 using random sampling techniques. The number of samples in this research was 34 students. The self-efficacy and learning motivation questionnaire consisted of 28 questions, and the student learning outcomes test questions consisted of 25 questions. The results of data analysis of the variable analysis of self-efficacy, learning motivation, and student learning outcomes with a correlation coefficient value of R_hit 0.585 t_table 0.3291 and a significant value of 0.002 with a significance level of 0.05 has a moderate correlation. This means that H_0 is rejected and H_a is accepted. The determination test results obtained were 34.2%. This research shows that "There is a positive relationship between Self-Efficacy and Learning Motivation with Student Learning Outcomes on Endocrine System Material at La Tansa High School."